Influences of Appearance-Behavior Congruity on Memory and Social Judgments - Cassidy, Brittany S. (Memory, 2014)
Prior work shows that appearance-behavior congruity impacts memory and evaluations. Building upon prior work, we assessed influences of appearance-behavior congruity on source memory and judgment strength to illustrate ways congruity effects permeate social cognition. We paired faces varying on trustworthiness with valenced behaviors to create congruent and incongruent face-behavior pairs. Young and older adults remembered congruent pairs better than incongruent, but both were remembered better than pairs with faces rated average in appearance. This suggests that multiple, even conflicting, valenced cues improve memory over receiving fewer cues. Consistent with our manipulation of facial trustworthiness, congruity effects were present in the strength of trustworthiness-related but not dominance judgments. Subtle age differences emerged in congruity effects when learning about others, with older adults showing effects for approach judgments given both high and low arousal behaviors. Young adults had congruity effects for approach, prosociality, and trustworthiness judgments, given high arousal behaviors only. These findings deepen our understanding of how appearance-behavior congruity impacts memory for and evaluations of others.